Black Lives Matter Protests, Social Distancing, and COVID-19 - Dhaval M. Dave; Andrew I. Friedson; Kyutaro Matsuzawa; Joseph J. Sabia; Samuel Safford (Institute of Labor Economics (IZA), 2020)
Sparked by the killing of George Floyd in police custody, the 2020 Black Lives Matter protests have brought a new wave of attention to the issue of inequality within criminal justice. However, many public health officials have warned that mass protests could lead to a reduction in social distancing behavior, spurring a resurgence of COVID-19. This study uses newly collected data on protests in 315 of the largest U.S. cities to estimate the impacts of mass protests on social distancing and COVID-19 case growth. Event-study analyses provide strong evidence that net stay-at-home behavior increased following protest onset, consistent with the hypothesis that non-protesters' behavior was substantially affected by urban protests. This effect was not fully explained by the imposition of city curfews. Estimated effects were generally larger for persistent protests and those accompanied by media reports of violence. Furthermore, we find no evidence that urban protests reignited COVID-19 case growth during the more than three weeks following protest onset. We conclude that predictions of broad negative public health consequences of Black Lives Matter protests were far too narrowly conceived.
Keywords: H75; I18; 330; coronavirus; social distancing; urban protests; COVID-19